Macrophages reprogramming driven by cancer-associated fibroblasts under FOLFIRINOX treatment correlates with shorter survival in pancreatic cancer - Zainab Hussain; Thomas Bertran; Pascal Finetti; Eugénie Lohmann; Émilie Mamessier; Ghislain Bidaut; François Bertucci; Moacyr Jesus Barreto de Melo Rêgo; Richard Tomasini (2024)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) remains a clinically challenging cancer, mainly due to limited therapeutic options and the presence of a highly prominent tumor microenvironment (TME), facilitating tumor progression. The TME is predominated by heterogeneous populations of cancer-associated fibroblasts (CAFs) and tumor associated macrophages (TAMs), in constant communication with each other and with tumor cells, influencing many tumoral abilities such as therapeutic resistance. However how the crosstalk between CAFs and macrophages evolves following chemotherapeutic treatment remains poorly understood, limiting our capacity to halt therapeutic resistance. Methods We combined biological characterization of macrophages indirectly cocultured with human PDAC CAFs, under FOLFIRINOX treatment, with mRNAseq analyses of such macrophages and evaluated the relevance of the specific gene expression signature in a large series of primary PDAC patients to search for correlation with overall survival (OS) after FOLFIRINOX chemotherapy. Results Firstly, we demonstrated that CAFs polarize naïve and M1 macrophages towards an M2-like phenotype with a specific increase of CD200R and CD209 M2 markers. Then, we demonstrated that CAFs counteract the pro-inflammatory phenotype induced by the FOLFIRINOX on Macrophages. Indeed, we highlighted that, under FOLFIRINOX, CAFs limit the FOLFIRINOX-induced cell death of macrophages and further reinforce their M2 phenotype as well as their immunosuppressive impact through specific chemokines production. Finally, we revealed that under FOLFIRINOX CAFs drive a specific macrophage gene expression signature involving SELENOP and GOS2 that correlates with shortened OS in FOLFIRINOX-treated PDAC patients. Conclusion Our study provides insight into the complex interactions between TME cells under FOLFIRINOX treatment. It suggests potential novel candidates that could be used as therapeutic targets in combination with FOLFIRINOX to prevent and alleviate TME influx on therapeutic resistance as well as biomarkers to predict FOLFIRINOX response in PDAC patients.